A New Genus and Species of Lophocateridae from Mid-Cretaceous Amber of Myanmar (Coleoptera) - Yu, Ya-Li; Li, Yan-Da; Kolibáč, Jiří; Ślipiński, Adam; Ren, Dong; Pang, Hong; Li, Zhi-Qiang (Insects, 2021)
A new genus and species of the cleroid family Lophocateridae are described and illustrated from the mid-Cretaceous amber of northern Myanmar. Gracilenticrus burmiticus Yu, Kolibáč & Ślipiński gen. et sp. nov. is unique among Lophocateridae in the tiny body size, frontoclypeal suture and antennal grooves absent, symmetrical antennal clubs, protrochantin reduced, tarsal claws small and widened at base. A key to the species of Mesozoic Lophocateridae is also provided. Morphological characters of the newly discovered Gracilenticrus were analyzed together with representatives of 43 extant genera of Cleroidea (broadly defined Trogossitidae) in a matrix of 91 characters. Gracilenticrus burmiticus was resolved as a member of Lophocateridae. The discovery of a diverse fauna of Lophocateridae in the mid-Cretaceous sheds a new light on the early evolution of superfamily Cleroidea.
Keywords: Burmese amber; Cretaceous; phylogeny; Lophocateridae